2014
DOI: 10.1080/15389588.2013.833329
|View full text |Cite
|
Sign up to set email alerts
|

Driving During Alcohol Hangover Among Dutch Professional Truck Drivers

Abstract: Driving with a hangover is a common phenomenon, and professional drivers acknowledge that their driving is impaired. Therefore, future experimental research should examine the magnitude of impairment while driving with an alcohol hangover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
0
37
0
1
Order By: Relevance
“…A recent study interviewing Dutch professional truck drivers revealed that in addition to causing significant socio-economic consequences, the alcohol hangover may also put those experiencing this post-intoxication state at increased traffic accident risk. This study showed that more than half of the professional drivers who consume alcohol and occasionally have hangovers report that they have driven while having a hangover during the past year, both private and professionally [8]. While most drivers admit to driving in the hangover state ‘sometimes’, about 10% of them state driving ‘often’ or ‘always’.…”
Section: Hangover Effects On Cognitive Functioning and Drivingmentioning
confidence: 99%
“…A recent study interviewing Dutch professional truck drivers revealed that in addition to causing significant socio-economic consequences, the alcohol hangover may also put those experiencing this post-intoxication state at increased traffic accident risk. This study showed that more than half of the professional drivers who consume alcohol and occasionally have hangovers report that they have driven while having a hangover during the past year, both private and professionally [8]. While most drivers admit to driving in the hangover state ‘sometimes’, about 10% of them state driving ‘often’ or ‘always’.…”
Section: Hangover Effects On Cognitive Functioning and Drivingmentioning
confidence: 99%
“…Over the past decade, several studies have examined the effects of alcohol hangover on cognitive performance and its impact on daily activities. With only a few exceptions (Collins & Chiles, ; Streufert et al, ; Taylor, Dolhert, Friedman, Mumenthaler, & Yesavage, ; Yesavage, Dolhert, & Taylor, ), studies consistently showed significant impairment during alcohol hangover on potentially dangerous daily activities such as driving a car (Laurell & Törnros, ; Törnros & Laurell, ; Verster et al, ; Verster, van der Maarel, McKinney, Olivier & de Haan, ), riding a bicycle (Hartung et al, ), flying an airplane (Morrow, Leirer, & Yesavage, ; Morrow et al, ; Petros et al, ; Yesavage et al, ; Yesavage & Leirer, ), and job performance such as ship power plant operation Rohsenow, Howland, Minsky, & Arnedt, ) or surgery (Kocher, Warwick, Al‐Ghnaniem, & Patel, ; Van Dyken, Szlabick, & Sticca, ). Nonetheless, a more comprehensive understanding of the alcohol hangover and its impact on cognition is required.…”
Section: Introductionmentioning
confidence: 99%
“…potentially dangerous daily activities such as driving a car (Laurell & Törnros, 1983;Törnros & Laurell, 1991;Verster, van der Maarel, McKinney, Olivier & de Haan, 2014), riding a bicycle (Hartung et al, 2015), flying an airplane (Morrow, Leirer, & Yesavage, 1990; Morrow et al, 1993;Petros et al, 2003;Yesavage et al, 1994;Yesavage & Leirer, 1986), and job performance such as ship power plant operation Rohsenow, Howland, Minsky, & Arnedt, 2006) or surgery (Kocher, Warwick, Al-Ghnaniem, & Patel, 2006;Van Dyken, Szlabick, & Sticca, 2013). Nonetheless, a more comprehensive understanding of the alcohol hangover and its impact on cognition is required.…”
mentioning
confidence: 99%
“…A driving simulator study has shown that highway driving is significantly impaired during the hangover state [8] and yet, 56.4% of the interviewed Dutch truck drivers admitted driving, both privately and professionally, while in a hangover state [6]. However, as most data was gathered using self-report surveys and laboratory experiments, little is known about real life consequences, including the actual risk of injury.…”
Section: Cognitive Effects Of the Alcohol Hangovermentioning
confidence: 99%